Загрози та виклики гонки ядерних озброєнь на сучасному етапі - Цвєтков, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2020)
Розглядаються актуалізовані проблеми ядерної зброї та гонки ядерних озброєнь у сучасному світі на переважно базі оцінок німецької
«Statista», Американської федерації вчених та Стокгольмського міжнародного інституту з досліджень миру. Акцентується, що винайдена
понад сімдесят років тому ядерна зброя не тільки не втратила своїх
базових якостей наймасовішого і наймасштабнішого ураження, але й
додала до цього новітні чинники глобальної загрози її розповсюдження
та викликів інноваційних технологічних звершень у засобах її доставки.
Останнє все частіше накладається на зростаючу конфліктність сучасного багатополюсного світоустрою і в такий спосіб додає стимулів до
глобальних змагань у накопичені усіх форм озброєнь ядерної сфери та
виділення на це ядерними і неядерними державами-акторами безпрецедентних фінансових коштів. Усвідомлення зазначених викликів та загроз
має стимулювати міжнародний діалог на захист принципу неподільності
миру у світі глобальної доби. Contemporary issues of nuclear weapons and the nuclear arms race in the
modern world are examined, based mainly on the assessments of the German
“Statista” company, the American Federation of Scientists and the Stockholm
International Peace Research Institute. It is emphasized that invented more
than seventy years ago, nuclear weapon has not lost its basic qualities of the
most massive and large-scale destruction, but also added to this the latest
factors of global threat of its proliferation and the challenges of innovative
technological advances in its means of delivery. The latter is increasingly
imposed on the growing conflict of the modern multipolarworld order, thereby
giving impetus to global competition in the accumulation of all forms of
nuclear weapons and allocating unprecedented financial resources from
nuclear and non-nuclear powers.
It is shown that the most fierce competition in the nuclear arms race is
developing in the triangle of relations and national interests between the US,
Russia and China. On the same fact base, it is argued that China cannot be
compared to the other two nations in the accumulated nuclear weapon
arsenals, but that its technological positions and growing military potential
lead to major changes in the bilateral concepts of international security and
even to the termination of a number of Russian-American treaty agreements,
above all in development of medium- and short-range ground-based missiles.
There is also a gradual transition to a new deployment of forces and global
strategies in the field of nuclear arms. World awareness of these changes is
needed in a kind of the Swedish proposal on implementation of strategy for the
“step-by-step” approach to nuclear disarmament. In general, challenges and
threats should stimulate international dialogue in defense of the principle of
peace-sharing in a global age.